Rational reconstructions of modern physics - Mittelstaedt, Peter (Dordrecht, Netherlands Springer Dordrecht, 2011)
assical physics and its underlying ontology are loaded with several metaphysical hypotheses that cannot be justified by rational reasoning nor by experimental evidence. Furthermore, it is well known that some of these hypotheses are not contained in the great theories of modern physics, such as the theory of relativity and quantum mechanics. This book shows that, on the basis of Newton?s classical physics and by rational reconstruction, the theory of relativity as well as quantum mechanics can be obtained by partly eliminating or attenuating the metaphysical hypotheses. Moreover, it is shown that these reconstructions do not require additional hypotheses or new experimental
Introduction -- Chapter 1: Rise and Fall of Physical Theories - The evolution of Modern Physics from the classical world - Intuitiveness and truth of Modern Physics - The new approach: Reduction of metaphysical hypotheses -- Chapter 2 : Reconstruction of Special and General Relativity - Historical Development versus rational reconstruction - Reconstruction of Special Relativity - Space-time intervals and Relativistic Mechanics - The numerical value of the constant w - Could Special Relativity have been discovered already by Newton? A pseudo-historical digression - The attempt to reconstruct General Relativity -- Conclusion - Chapter 3: Reconstruction of Quantum Mechanics - The Historical Development of Quantum Mechanics - The reduction of ontological hypotheses.- The Formal Languages of Classical Physics and of Quantum Physics -  The approach to orthomodular quantum logic - The bottom-top reconstruction of QM in Hilbert space - Physics of Indistinguishable Objects - Are the laws of Quantum Logic laws of nature? - Quantum physics and classical physics ? their respective roles -- Chapter 4 : Three constants of Nature - The problem of constants of nature in modern physics - The meaning of constant c in modern physics - Planck?s constant h in the light of quantum logic - The problem of the gravitational constant k -- Three Constants of Nature: concluding remarks - Chapter 5: Interpretations of modern physics -  Introductory remarks - Two Interpretations - Summary - Chapter 6: Concluding remarks - Intuitiveness and truth in physical theories - Ref
Electronic reproduction.
Keywords: Relativity (Physics) .